Kompetensi Profesional Guru PAI dalam Mengintegrasikan Nilai-Nilai Islam dalam Pembelajaran di MTs Wadi Mubarak - Suriyati Suriyati; Rahmatullah Rahmatullah; Kahar Kahar; Mustamir Mustamir; Khairil Syam (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2026)
This study aims to describe and analyze the professional competence of Islamic Religious Education (PAI) teachers in integrating Islamic values ​​into the learning process at MTs Wadi Mubarak. The professional competence of PAI teachers includes a broad and in-depth mastery of teaching materials, the ability to develop effective learning strategies, and the ability to relate the material to the values ​​of faith, worship, and morals in the daily lives of students. This study used a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used data reduction, data presentation, and drawing conclusions. The results of the study indicate that Islamic Religious Education teachers have integrated Islamic values ​​in lesson planning, implementation of teaching and learning activities, and evaluation, emphasizing cognitive, affective, and psychomotor aspects. This integration is carried out through role models, habituation of worship, and strengthening of Islamic character. However, there are still obstacles such as limited time and innovation in learning methods. Therefore, continuous improvement of teacher professional competence is essential.